Effect of thinning and shade removal on green stem disorder in soybean. (3rd April 2018) - Yamazaki, Ryo; Katsube-Tanaka, Tomoyuki; Shiraiwa, Tatsuhiko
Abstract: Green stem disorder (GSD) in soybean ( Glycine max (L.) Merrill) retains green stems and leaves as the pods mature, thereby reducing the harvest efficiency and impairing seed quality. In order to elucidate the causes of GSD, the factors that promote GSD need to be identified. In our experiments, we adjusted plant density at the developmental growth stage R1 (the beginning of flowering) or at R5 (the beginning of seed filling), from dense (22.2 plants m –2 ) to sparse (5.56 plants m –2 ) by thinning. We found that GSD occurrence was increased when plant density was changed, compared to the treatments that were maintained under either dense or sparse conditions. GSD was promoted more strongly when thinning was conducted at R5 than at R1 stage. Shading equipment surrounding plants, except for their upper-most leaves, was implemented to determine the association of shading and GSD. The results of the shade experiment revealed that GSD occurrence generally increased in treatments subjected to shade removal, compared to those that were shaded until R8 stage (full maturity) or never shaded since the time of sowing. GSD was strongly promoted by shade removal at R5 than at R1 stage. The shading results coincide with the results of the plant density experiment, indicating that an increase in light availability enhances source activity relative to sink at R5 stage, thereby promoting GSD occurrence in soybean. Thinning is expected to be used as an easy experimental method to create GSD for research purpose.